An in-depth investigation of ground jerk characteristics for the four strongest Vrancea (Romania) earthquakes in the past half-century - Craifaleanu, Iolanda-Gabriela (Frontiers in Built Environment, 2025)
A significant number of studies on seismic jerk have been performed worldwide in the past few years, dealing with its various features and applications in the assessment and mitigation of earthquake effects on buildings. However, there are only a few studies based on a regional approach, aimed to investigate jerk characteristics and impact for a particular seismic source, geological setting and local built environment features. The present research focuses on the Vrancea seismogenic source in Romania. Characterized by a very peculiar subduction mechanism, with a seismic activity unique in Europe and rarely found in other parts of the world, Vrancea has generated, only in the past half century, four destructive earthquakes with moment magnitudes greater than 6, that affected large areas, including some within the neighboring countries. By using a database of over 300 accelerograms, a detailed study of ground jerk characteristics, including their mapping, was conducted. Special consideration was given to the Mw = 7.4 4 March 1977, earthquake, the strongest of all analyzed. The only complete three-component accelerogram that is available from this event led to a radical revision of the national seismic code, due to its unexpected features. The results of the current research, to the author’s knowledge the first one on this topic addressing the Vrancea source, are meant to shed a new light on some less-known characteristics of ground motions recorded from strong earthquakes that hit Romania during the past 5 decades and to provide information that would further substantiate, on a more extensive scientific basis, the seismic risk assessment of the entire region. This first phase of the study is planned to be continued with an analysis of jerk impacts at structure level, as well as with the investigation of other related topics, addressing current challenges in the field, as presented in the final section of the article.